Remembering Julius C. Allen - Pressley, T.A. (Cellular and Molecular Biology, 2007)
Our respected colleague and friend, Dr. Julius C. Allen, passed away on Thursday, February 10, 2005. Known to his friends and family as "Julie," Dr. Allen was an internationally-recognized investigator in cardiovascular science and an early contributor to the biochemistry of the Na,K-pump. His work was inevitably multi-disciplinary, with contributions to biochemistry, physiology, and pharmacology. He helped develop and later directed the Graduate Program for Cardiovascular Sciences at Baylor College of Medicine. Beyond his science, Dr. Allen was a strong advocate of progressive social and political reform, as well as a passionate sports enthusiast. With his sense of humor, it was impossible not to have a good time when he was around. His friendship, wise advice, and experience will be sorely missed.